Exenatide Protects Against Cardiac Dysfunction by Attenuating Oxidative Stress in the Diabetic Mouse Heart - Ding, Wei; Chang, Wen-guang; Guo, Xiao-ci; Liu, Ying; Xiao, Dan-dan; Ding, Dan; Wang, Jian-xun; Zhang, Xue-juan (Frontiers in Endocrinology, 2019)
Cardiovascular disease is the major cause of death in patients with diabetes. Current treatment strategies for diabetes rely on lifestyle changes and glucose control to prevent angiopathy and organ failure. Exenatide, a glucagon-like peptide-1 (GLP-1) receptor agonist, is used as an add-on therapy to insulin treatment. Exenatide also has multiple beneficial effects in addition to its hypoglycemic effects, such as preventing hepatic steatosis and protecting against cardiac injury from doxorubicin-induced cardiotoxicity or ischemic reperfusion. However, the mechanisms underlying the cardioprotective effects of exenatide in diabetes have not been fully clarified. To address this issue, we investigated the cardioprotective effects of exenatide in type 1 and type 2 diabetic mice. We found that exenatide simultaneously attenuated reactive oxidative species (ROS) production through increases in the antioxidant enzymes manganesedependent superoxide dismutase (MnSOD) and catalase. Moreover, exenatide decreased tumor protein P53 (p53) expression and prevented cell apoptosis in H9c2 cells. The presence of the catalase inhibitor 3-AT attenuated the effects of exenatide. Overall, the results strongly indicate that exenatide treatment may be protective against the development of diabetic cardiomyopathy.